c-Src Increases the Sensitivity to TKIs in the EGFR-Mutant Lung Adenocarcinoma - Min, Weili; He, Chenyang; Zhang, Shuqun; Zhao, Yang (Frontiers in Oncology, 2021)
c-Src and the epidermal growth factor receptor (EGFR) are key apical kinases that govern cell responses to microenvironmental cues. How c-Src affects EGFR-related signaling and targeted therapy remains elusive. Initially, caspase-8 phosphorylated at tyrosine 380 by c-Src predominantly enhancing c-Src activation to facilitate metastasis through attaining epithelial-mesenchymal transition (EMT) phenotype in lung adenocarcinoma. Mechanistically, the linkage of c-Src SH2 domain with phosphotyrosine 380 of caspase-8 and SH3 domain with “PDEP” motif of caspase-8 overactivates c-Src as compared with other c-Src-partner proteins. c-Src is incapable of triggering EGFR-related signaling. This is reflected by the levels of phosphotyrosine 1068, 1086, and 1145, which have no impact on c-Src activation. Tyrosine kinase inhibitors (TKIs) suppress EGFR-related signaling to yield cell deaths of lung adenocarcinoma by both necroptosis and intrinsic apoptosis. Given that c-Src activation is frequent in lung adenocarcinoma, blocking c-Src activation through dasatinib can seal the survival-signaling-related phosphotyrosines of EGFR by its SH2 domain, which in turn increases the antitumor activity of TKIs in EGFR-mutant lung adenocarcinoma. Collectively, c-Src inactivation by dasatinib administration sensitizes EGFR-mutant lung adenocarcinoma to TKIs.